Short Term Outcomes of Percutaneous Pulmonary Balloon Valvuloplasty in Adult Patients with Pulmonary Stenosis - Almyahi, Mohammed H.; AI-Ugaidy, Yassen Hadi; Alkmani, Tahsin A.; Alkubaisy, Omar K. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Percutaneous Balloon Pulmonary Valvuloplasty (BPV) is now the treatment of choice for pulmonary valve stenosis (PS) Patients and Methods. It is a retrospective study involving 40 consecutive patients with moderate to severe PS underwent BPV in Ibn Albitar Hospital for Cardiac Surgery from Sept. 2003 to Sept. 2004 , were medical records , Electrocardiograms ( ECG ) , Echo Doppler studies , and Catheterization data were reviewed carefully. Results: Mean pressure gradient across pulmonary valve (PV) was reduced from 112 +/- 46 mmHg before intervention to 49 It/- 34.7 after intervention. Procedure failure occurred in one patient (2.5 %), four patients (10%) developed mild to moderate pulmonary regurgitation , no mortality was detected. Conclusion: BPV is effective and safe procedure for patients with valvular PS.